STRUCTURE, MICROSTRUCTURE, AND PIEZOELECTRIC PROPERTIES OF KNLNS-BNKZ LEAD-FREE CERAMICS UNDER THE EFFECT OF DIFFERENT SINTERING TEMPERATURES - Phan Dinh Gio; Huynh Thi Chi; Le Tran Uyen Tu; Nguyen Truong Tho (Tạp chí Khoa học Đại học Đà Lạt)
Samples of 0.96(K0.48Na0.48Li0.04)(Nb0.95Sb0.05)O3-0.04Bi0.5(Na0.82K0.18)0.5ZrO3 piezoelectric ceramic were fabricated with conventional ceramic techniques and sintered at different temperatures. The effect of sintering temperature (TS) on the structure, microstructure, and piezoelectric properties of the ceramics was studied in detail. The experimental results showed that with an increase of the TS temperature, the structure of the ceramics transformed from an orthorhombic-tetragonal mixed phase (O-T) at TS £ 1100 °C into a rhombohedral-tetragonal (R-T) mixed phase with a dense microstructure of uniform grain size at TS = 1110 °C. When TS was further increased (TS ³ 1120 °C), the ceramics showed only a rhombohedral phase (R). The ceramics showed the best electrical properties for TS = 1110 °C at which the rhombohedral and tetragonal (R-T) phases coexist. Specifically, the ceramic density reached its highest value (4.22 g/cm3), the electromechanical coupling coefficients kp and kt were 0.46 and 0.50, respectively, and the piezoelectric coefficient d33 was 245 pC/N.